IMPLEMENTATION OF QUR'ANY LYRICS AND SONGS BY KH.M. QOYYIM YA'QUB TO INCREASE THE UNDERSTANDING OF RELIGION IN JAMA'AH ASSEMBLY TA'LIM AT-TAUBAH IN DATAR LEBAR VILLAGE, BENGKULU - Laila Bella (Media Inovasi Pendidikan dan Publikasi, 2023)
The focus of this research: How is the implementation and implications of the verses and songs of the Qur'any by KH. M. Qoyyim Ya'qub to increase understanding of religious knowledge in the Congregation of the Ta'lim At-Taubah Assembly. the aims of the research are 1) to analyze how the implementation of verses and songs of the Qur'any by KH. M. Qoyyim Ya'qub to increase understanding of religious knowledge in the Congregation of the Ta'lim At-Taubah Assembly. 2) Analyzing the implications of KH. M. Qoyyim Ya'qub to increase understanding of religious knowledge in the Congregation of the Ta'lim At-Taubah Assembly. This approach uses a qualitative approach, a type of case study research. Data collection techniques are Observation, Interview, and Documentation. Data analysis techniques are data reduction, data presentation and drawing conclusions. The validity of the data is increasing persistence, triangulation and discussion of findings. As for the findings or results of this study, 1) Implementation of the congregation of the At-Taubah Ta'lim Assembly in Datar Lebar Bengkulu Village consists of two activity steps, namely planning and implementation. Planning in activities includes objectives, materials, methods, and media. Its implementation begins with reciting the Al-Qur'an in rotation, explaining the makhrojul letters and the science of tajwid. explains the relationship between the verses read earlier and the Qur'any Lyrics, sings the Qur'anic Poems and Songs by imitating and explaining the meaning contained in the Qur'anic Poems and Songs. 2) Implementation of Qur'any Poems and Songs for the congregation of the At-Ta'lim Ta'lim Assembly has implications for increasing understanding of religious knowledge so that the Jama'ah Majelis Ta'lim will get closer to Allah, the Jama'ah Majelis Ta'lim will understand more contents of the contents of the Qur'an, the Jama'ah Majelis Ta'lim will understand the explanation better than the Qur'any Poems and Songs, the Jama'ah Majelis Ta'lim will apply the understanding of religious knowledge in everyday life, the Jama'ah Majelis Ta'lim will be a good example for other communities